The Self-Regulation of Learning – Self-Report Scale for Sport Practice: Validation of an Italian Version for Football - Reverberi, Eleonora; Gozzoli, Caterina; D’Angelo, Chiara; Lanz, Margherita; Sorgente, Angela (Frontiers in Psychology, 2021)
Self-regulation of learning (SRL) is a key psychological factor that supports young athletes aiming to reach the elite level by promoting their involvement in deliberate practice. We contributed to the validation of the Italian version of the Bartulovic et al. (2017) Self-Regulation of Learning‒Self-Report Scale for Sport Practice by testing its factorial structure, reliability and measurement invariance among elite and non-elite football players, involving 415 male professional, semi-professional and amateur youth academy players (Mage = 16.2, SD = 1.51). The original six-factor structure (planning, reflection, effort, self-efficacy, self-monitoring and evaluation) did not fit the data well and a five-factor solution (where self-monitoring and evaluation items load on the same factor, named “self-supervision”) was a better fit. This five-factor solution was measurement invariant across groups of elite and non-elite athletes. We found that elite athletes scored significantly higher than non-elite ones in each SRL subprocess. Implications for future validation studies and for the use of this tool are discussed.